Sensorineural hearing loss in patients with tubotympanic type of chronic suppurative otitis media: a prospective study - Singh, Manjit; Aman, Mohd; Prakash, Om; Suri, Anil; Bala, Kiran; Sharma, Rupali; Sharma, Preeti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Chronic suppurative otitis media (CSOM) is defined as a chronic inflammation of the mucosa of the middle ear cleft, which presents with recurrent or persistent ear discharge through a tympanic membrane perforation. Hearing loss associated with CSOM is conductive but sensorineural hearing loss has also been observed which may be due to toxins produced during infection that can damage the hair cells on the basal turn of the cochlea. To study the relationship between sensorineural hearing loss (SNHL) and tubotympanic type of Chronic Suppurative Otitis Media. Methods: This was a prospective study conducted on 60 patients of tubotympanic type of CSOM attending the ENT OPD at SMGSH, Jammu after getting (Institutional Ethical Committee) IEC clearance. Results: In the present study, 8 (13.3%) out of 60 patients of tubotympanic or mucosal type of CSOM had SNHL. Conclusions: Although it is a known fact that tubotympanic type of CSOM causes conductive hearing loss due to perforation in the tympanic membrane and ossicular damage but it is concluded from the present study that tubotympanic type of CSOM carries a risk of SNHL in significant percentage of patients. Hence, it is advocated that patients should be made aware of risk of development of SNHL in tubotympanic type of CSOM if left unoperated for a longer duration.